Analysis of Main Trends and Development Directions in the Field of Retail Banking Services - Rayimnazarov Salokhiddin Davirbek (International Journal on Economics, Finance and Sustainable Development, 2022)
this article examines the main trends observed in the field of retail banking services, their nature and impact on transformational processes. In addition, a dynamic analysis of the results of the activity of the "Monzo" bank, which specializes in providing retail banking services, was carried out. On the basis of the conducted research, relevant conclusions and proposals were developed.